SOME PROBLEMS OF TRAINING FOREIGN CITIZENS AT THE INSTITUTE OF CULTURE - S. V. Butsyk; N. A. Zhernokova; O. G. Usanova (Высшее образование в России)
The article touches upon the problems of training foreign citizens at a higher education institution (the sphere of culture) located in a relative distance from the capital region (Urals Federal District). The authors present the results of a study of the motives for entering the University by different groups of foreign students - citizens of Tajikistan, Kazakhstan and far abroad countries. The authors have analyzed the main similarities and differences between the groups selected for the study such as: 1) the main motives for entering a Russian university of culture; 2) the presence of anxiety before entry into Russian Federation and change of this feeling during the first weeks of stay in the educational organization. The paper reveals the key factors affecting the adaptation offoreign students during the initial period of training.